Analisis Risiko Pekerjaan Erection Jembatan Kereta Api Menggunakan Metode Fuzzy FMEA - Astuti, Septiana Widi; Nurjanah, Melania Uswatul; Nurhadi, Muhammad (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The Solo-Semarang dual railway line project is considered to have a high risk of danger because it is located very close to level crossings and becomes a meeting between seven roads so that it can endanger residents and the environment as well as project workers who are in the project area. The purpose of this study is to conduct a risk assessment using the Fuzzy Failure Mode And Effect Analysis (FMEA) method of hazards or potential incidents in railroad bridge erection work. The Fuzzy FMEA method is used to identify work accident risks and determine risk mitigation priorities based on the highest Fuzzy RPN (Risk Priority Number) value. The results of the research conducted from March - April 2023 obtained 14 (fourteen) risks obtained from observations and Job Safety Analysis documents. Based on the processing results, the highest Fuzzy RPN value was obtained in the erection work of 500 (five hundred) for the risk of machine damage. This value is in the high category so that risk mitigation actions are needed to prevent and reduce the impact of risks.